Changes over time in canine retraction: An implant study - Martins, Renato Parsekian [UNESP]; Buschang, Peter H.; Gandini Júnior, Luiz Gonzaga [UNESP]; Rossouw, P. Emile (Mosby-elsevier, 2009)
Introduction: The objective of this study was to analyze rates of canine movement over the first 2 months of continuous retraction, when rate changes are expected. Methods: Ten patients with bone markers placed in the maxilla and the mandible had their canines retracted over a 2-month period. Retraction was accomplished with beta-titanium alloy T-loop springs. Standardized 45 degrees oblique cephalograms where taken initially and every 28 days thereafter. The radiographs were scanned and digitized twice (the average was used for the analyses). The radiographs were superimposed by using the bone markers and oriented on the functional occlusal plane. Paired t tests were used to compare side and jaw effects. Results: There were no significant differences between sides. The maxillary cusp was retracted 3.2 mm, with less movement during the first (1.1 mm) than during the second 4 weeks (2.1 mm). The maxillary apices did not move horizontally. There were no significant vertical movements in the cusps and apices of the maxillary canines. The mandibular cusp was retracted 3.8 mm-1.1 mm during the first and 2.7 mm during the second 4 weeks. The mandibular apices were protracted 1.1 mm. The cusps and apices were intruded 0.6 and 0.7 mm, respectively. The only difference between jaws was the greater protraction of the mandibular apices during the second 4 weeks and in overall movement. Conclusions: The rate of canine cusp retraction was greater during the second than the first 4 weeks. The mandibular canines were retracted by uncontrolled tipping whereas the maxillary canines were retracted by controlled tipping. (Am J Orthod Dentofacial Orthop 2009; 136: 87-93)